(untitled) (Polish Yearbook of International Law, 2025)
This article argues that better engagement between international law and time requires us to unpack the contingent memories and imaginaries that underpin international legal regimes and processes. We as a field need to move away from thinking of time as static and linear. International Cultural Heritage Law (ICHL) is an ideal case study to think through these relationships, given the subfield’s connection to identity and its relative openness to different epistemologies. This article assesses the work that time does in shaping international law, working through the three linear dimensions of time (past, present and future) to highlight the limits of internation al law, and in shaping the heuristics of these three linear dimensions. ICHL offers a pathway to simultaneously showcase the shortcomings of our international legal understandings of time (which I dub chrononormative), and to imagine different possibilities that better advance the human goals that should be the foundation and the goal of international legal norms and regimes.